2016
DOI: 10.3758/s13414-016-1079-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory cueing effects following manual and saccadic responses to arrow cues

Abstract: With two cueing tasks, in the present study we examined output-based inhibitory cueing effects (ICEs) with manual responses to arrow targets following manual or saccadic responses to arrow cues. In all experiments, ICEs were observed when manual localization responses were required to both the cues and targets, but only when the cue-target onset asynchrony (CTOA) was 2,000 ms or longer. In contrast, when saccadic responses were made in response to the cues, ICEs were only observed with CTOAs of 2,000 ms or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Concerning stimulus-response repetition costs, Spadaro et al (2012) have demonstrated their robustness in simple stimulus-identification tasks with intervening response events. Perhaps more importantly still, recent data suggest that stimulus-response repetition costs may be observed in simple stimulus-identification tasks at fixation without intervening response events, as long as the interval between the cue and target is extended beyond the typical CTOA (Ding, He, Satel, & Wang, 2016;Avery, Cowper-Smith, & Westwood, 2015). It thus appears as if, at least in relatively simple two stimulus identification tasks at fixation, some form of inhibition may-eventually-follow from the initial cue representation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning stimulus-response repetition costs, Spadaro et al (2012) have demonstrated their robustness in simple stimulus-identification tasks with intervening response events. Perhaps more importantly still, recent data suggest that stimulus-response repetition costs may be observed in simple stimulus-identification tasks at fixation without intervening response events, as long as the interval between the cue and target is extended beyond the typical CTOA (Ding, He, Satel, & Wang, 2016;Avery, Cowper-Smith, & Westwood, 2015). It thus appears as if, at least in relatively simple two stimulus identification tasks at fixation, some form of inhibition may-eventually-follow from the initial cue representation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the neurophysiological evidence neither rules out nor confirms the possibility of eye movements being affected by retrieval-based binding processes. However, given some rather distinct pathways for saccade generation opens up the possibility of effector-specificitywhich might be the reason for differences that have been previously observed between manual and eye responses (e.g., for inhibition-related effects, Ding et al, 2016;Eng et al, 2017;Malienko et al, 2018;Taylor & Klein, 2000;in Hick's law, Kveraga et al, 2002;Lawrence et al, 2008;see Proctor & Schneider, 2018, for a review; localization responses to moving targets, Lisi & Cavanagh, 2017; and several other tasks, see Bompas et al, 2017). Moreover, the joint Simon effect (Sebanz et al, 2003) is not observed for saccadic responses (Liepelt et al, 2019), thus raising doubt that all actions are processed in the same way irrespective of the effector involved.…”
Section: Introductionmentioning
confidence: 99%